Simulating the PM2.5 in southern Taiwan under high-pressure return flow during the Kao-Ping Experiment (KPEx) - Ming-Tung Chuang; Charles C.K. Chou; Chuan-Yao Lin; Wei-Che Lin; Neng-Huei Lin; Wei-Nai Chen; Steven Soon-Kai Kong (Atmospheric Research, 2027)

Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Long-term exposure to PM2.5-bound metals and female breast cancer incidence in New Mexico, USA - Yanhong Huang; Charles L. Wiggins; Angela L. W. Meisner; Yan Lin; Li Luo; Xi Gong (Air Quality, Atmosphere & Health, 2026)
Female breast cancer (FBC) is the most commonly diagnosed malignant cancer and the second leading cancer cause of death among women in the United States. Environmental exposures, particularly PM 2.5 -bound metals, have been increasingly associated with breast cancer incidence. We evaluated associations between long-term residential exposure to PM 2.5 -bound metals and age-adjusted FBC incidence rate at the census tract level in New Mexico from 1997 to 2019. FBC records were obtained from the New Mexico Tumor Registry. Annual metal exposure intensities for chromium, cobalt, copper, manganese, and mercury were estimated using a calibrated Emission Weighted Proximity Model (EWPM) over a 10-year pre-diagnosis window. Generalized Estimating Equations (GEE) with Gaussian estimation was used to estimate rate ratio (RR) for the association between PM 2.5 -bound metal exposure and FBC incidence in New Mexico. Exposure to PM 2.5 -bound chromium (adjusted RR 1.07, 95% CI: 1.05, 1.08), cobalt (adjusted RR 1.08, 95% CI: 1.05, 1.11), copper (adjusted RR 1.06, 95% CI: 1.04, 1.07), manganese (adjusted RR 1.05, 95% CI: 1.02, 1.08), and mercury (adjusted RR 1.05, 95% CI: 1.03, 1.07) show significant associations with increased FBC incidence rate. When exposure was categorized as unexposed, low, medium, and high groups, a significant increasing trend was observed across all five metals. Long-term exposure to multiple PM 2.5 -bound metals is associated with elevated FBC incidence rate in New Mexico. These findings highlight the need for further research and to biologically validate the observed associations and clarify potential mechanisms linking PM 2.5 -bound metal exposure to FBC incidence risk.

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Proteomic insights into intestinal immune modulation in Atlantic salmon (Salmo salar) fed fucoidan from brown seaweed (Saccharina latissima) - Kathiresan Purushothaman; Byron Morales-Lange; SérgioD.C. Rocha; Lin Qingsong; Luis Mercado; Margareth Øverland; Charles McLean Press (Fish & Shellfish Immunology, 2026)

Interrelationships among PM2.5/O3 concentrations, polluted weather patterns, and meteorological conditions over Taiwan based on 2006–2024 observations - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Meng-Hsuan Lee; Ja-Huai Lee; Chih-Chung Chang; Wei-Nai Chen; Chian-Yi Liu (Atmospheric Research, 2026)

Industrial air pollution and lung and bronchus cancer survival in New Mexico, USA - Xi Gong; Yanhong Huang; Charles L. Wiggins; Angela L. W. Meisner; Yan Lin; Li Luo (Cancer Causes & Control, 2026)
Purpose Lung and bronchus cancer (LBC) is the leading cause of cancer-related deaths. This study examines the relationship between exposure to industrial air pollution and lung and bronchus cancer survival (LBCS) in New Mexico, USA, from 1990 to 2019. Methods This retrospective cohort study included data from 18, 273 lung and bronchus cancer patients. Residential exposure to nine industrial air pollutants was estimated for each patient using the Emission Weighted Proximity Model (EWPM), which integrates industrial air emission data and air quality monitoring data form the U.S. Environmental Protection Agency’s (EPA). Cox proportional hazards modeling was applied to identify industrial air pollutants as decreased LBCS risk factors, adjusting for age at diagnosis, gender, cancer stage, race/ethnicity, smoking prevalence, and urbanization of residential address. Results Results show that residential exposure to 1,1,1-trichloroethane and cobalt during the survival period was significantly associated with decreased LBCS (adjusted hazard ratio [adjHR] for 1,1,1-trichloroethane: 1.06, 95% CI: 1.04, 1.09 and adjHR for cobalt: 1.06, 95% CI: 1.03, 1.09) compared to those unexposed among all patients. When exposure levels were categorized into four groups (unexposed, low, medium, high) based on annual average exposure during the survival period, the associations remained consistent. Conclusion This study underscores the negative influence of industrial air pollution on LBCS and emphasizes the need for targeted public health interventions in high-exposure areas.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

An in vitro-in silico workflow for predicting renal clearance of environmental chemicals and drugs - Courtney Sakolish; Hsing-Chieh Lin; Haley L. Moyer; Lucie C. Ford; Charles H. Christen; Barbara A. Wetmore; Michael J. DeVito; Philip Hewitt; Stephen S. Ferguson; Farah Raad; Ivan Rusyn; Weihsueh A. Chiu (Toxicology, 2026)

How effective are green roofs as building carbon sinks? Empirical evidence linking substrate, depth, and vegetation dynamics in the U.S. Great Plains - M.M. Lekhon Alam; Lee R. Skabelund; Charles W. Rice; James S. Lin; Jaeyoung Ha (Journal of Environmental Management, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Dietary yeast improves zebrafish immunity and survival against Aeromonas infection - Kathiresan Purushothaman; Sérgio D.C. Rocha; Daanish Kaul; Aleksandar B. Goksu; Byron Morales-Lange; Alexander D. Crawford; Liv Torunn Mydland; Henning Sørum; Lin Qingsong; Shubha Vij; Margareth Øverland; Charles McL. Press (Fish & Shellfish Immunology, 2025)

Exploring the bioactive properties of fucoidan from Sugar kelp to modulate the immune response and gut microbiota of Atlantic salmon - Sérgio D.C. Rocha; Byron Morales-Lange; Ruth Montero; Leszek Michalak; Purushothaman Kathiresan; Charles McLean Press; Luis Mercado; Qingsong Lin; Liv Torunn Mydland; Margareth Øverland (Food Bioscience, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Does the gall-forming cecidomyiid enhance host plant leaves and their phytochemicals? A case study of Bruggmanniella litseae (Diptera: Cecidomyiidae) - Charles Ko-Hsuan Wang; Sheng-Feng Lin; Hieng-Ming Ting; Man-Miao Yang; Meng-Yuan Huang (Arthropod-Plant Interactions, 2025)

Celebrating the fifth edition of the International Symposium on Fungal Stress – ISFUS, a decade after its 2014 debut - Alene Alder-Rangel; Amanda E.A. Rangel; Arturo Casadevall; Asiya Gusa; Chaoyang Xue; Charles M. Boone; Chris Todd Hittinger; Claudio A. Masuda; Consuelo Olivares-Yañez; Deborah Bell-Pedersen; Erica J. Washington; Gerhard Braus; et al. (Fungal Biology, 2025)

Exploration of complex physical and chemical processes of a severe haze episode over central Taiwan - Chuan-Yao Lin; Wen-Mei Chen; Yang-Fan Sheng; Wan-Chin Chen; Hing Cho Cheung; Charles; C.K. Chou (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Molecular dynamics simulation revealing the interactions between toxic aldehydes and starch: A case study of malondialdehyde, 4-hydroxy-2-hexenal, and 4-hydroxy-2-nonenal in starch-based food during frying - Feng Wang; Xianhong Bi; Yun Cui; Kewei Lin; Charles Brennan; Soottawat Benjakul; Gengsheng Xiao; Lukai Ma (Food Chemistry, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Harmonising flavours: How arousing music and sound influence food perception and emotional responses - Yi Hsuan Tiffany Lin; Daniel Shepherd; Kevin Kantono; Charles Spence; Nazimah Hamid (International Journal of Gastronomy and Food Science, 2025)

Challenges to and importance of considering early and intermediate ontogenetic stages in mangrove forest recovery and restoration - Taylor M. Sloey; Sean P. Charles; Lin Xiong; Edward Castañeda-Moya; Erik S. Yando; David Lagomasino (Marine Pollution Bulletin, 2024)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

PM2.5 episodes in northern Taiwan under southerly winds in late winter - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Meng-Hsuan Li; Shyh-Wei Chen; Shu-Hao Chang (Atmospheric Research, 2024)

Source apportionment of PM2.5 episodes in the Taichung metropolitan area, Taiwan - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Ja-Huai Lee; Meng-Hsuan Li; Wei-Nai Chen; Chih-Chung Chang; Chian-Yi Liu; Yi-Chun Chen (Atmospheric Research, 2024)

Toxicity, mutagenicity, and source identification of polycyclic aromatic hydrocarbons in ambient atmosphere and flue gas - Shih Yu Pan; Ya Syuan Wu; Yu-Cheng Chen; Yen-Shun Hsu; Yu Chi Lin; Pao Chen Hung; Charles C.-K. Chou; Somporn Chantara; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Science and Pollution Research, 2024)
This study aimed to assess the characteristics of particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs) from various stationary and mobile emission sources in Taiwan, with a focus on source apportionment and associated health risks. The northern power plant, equipped with bag filters operating at 150 °C, had significantly lower FPM and CPM levels (0.44 and 0.13 mg/m 3 , respectively) compared to the central and southern power plants, which used electrostatic precipitators operating at 250 °C (FPM, 1.45–8.35 mg/m 3 ; CPM, 2.37–3.73 mg/m 3 ). Additionally, emissions from diesel vehicles under both idle and high-speed conditions exhibited higher FPM levels (3.46–4.67 mg/m 3 ) than gasoline vehicles (0.19–0.40 mg/m 3 ). In terms of PAH toxicity, diesel vehicle emissions had significantly higher BaP-TEQ (87.3 ng/m 3 ) and BaP-MEQ (25.9 ng/m 3 ) levels compared to power plants (BaP-TEQ, 5.49 ng/m 3 ; BaP-MEQ, 2.65 ng/m 3 ). The highest ambient concentrations of PM2.5, BaP-TEQ, and BaP-MEQ were recorded at traffic sites, with values of 48 ± 36 µg/m 3 , 0.29 ng/m 3 , and 0.11 ng/m 3 , respectively. Differences in PAH distributions between stationary and mobile sources were influenced by factors such as pollution control technologies, combustion temperatures, and fuel types. Diesel vehicle emissions were dominated by benzo[g,h,i]perylene (BghiP), indeno[1,2,3-cd]pyrene (IND), benzo[a]pyrene (BaP), and benzo[b]fluoranthene (BbF) under idle conditions, while phenanthrene (PA), pyrene (Pyr), and BghiP were prevalent under high-speed conditions. Source apportionment conducted using principal component analysis (PCA) and positive matrix factorization (PMF) identified diesel and gasoline vehicles as the dominant contributors to atmospheric PAHs in Taiwan, accounting for 38% of the total, followed by coal-fired power plants at 35%. The highest lifetime excess cancer risk (ECR) of 2.5 × 10⁻ 5 was observed in traffic-dense areas, emphasizing the public health implications of vehicle emissions. The study adds credibility to the source apportionment findings, and the health risk analysis highlights variations across different regions, including traffic, urban, rural, and background zones.

The aroma profiles of dried gonggans: Characterization of volatile compounds in oven-dried and freeze-dried gonggan - Dongjie Liu; Qiaomei Shen; Kewei Lin; Feng Wang; Zhibin Bu; Jian Peng; Charles Brennan; Soottawat Benjakul; Gengsheng Xiao; Lukai Ma (Food Research International, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

GmSABP2-1 encodes methyl salicylate esterase and functions in soybean defense against soybean cyst nematode - Jingyu Lin; Weijiao Wang; Mitra Mazarei; Nan Zhao; Xinlu Chen; Vincent R. Pantalone; Tarek Hewezi; Charles Neal Stewart; Feng Chen (Plant Cell Reports, 2024)

Hysteresis area at the canopy level during and after a drought event in the Central Amazon - Bruno O. Gimenez; Daisy C. Souza; Niro Higuchi; Robinson I. Negrón-Juárez; Israel de Jesus Sampaio-Filho; Alessandro C. Araújo; Adriano J.N. Lima; Clarissa G. Fontes; Kolby J. Jardine; Charles D. Koven; Lin Meng; Gilberto Pastorello; et al. (Agricultural and Forest Meteorology, 2024)

Characteristics and impacts of fine particulates from the largest power plant plume in Taiwan - Ming-Tung Chuang; Charles C.-K Chou; Chung-Te Lee; Ja-Huai Lee; Wei-Che Lin; Chuan-Yao Lin; Wei-Nai Chen; Yi-Ying Chen; Kai-Hsien Chi (Atmospheric Pollution Research, 2024)

Variability and distribution of nighttime equatorial to mid latitude ionospheric irregularities and vertical plasma drift observed by FORMOSAT-5 Advanced Ionospheric Probe in-situ measurements from 2017 – 2020 - Loren C. Chang; Yueh-Chun Hsieh; Chi-Kuang Chao; Yi Duann; Cornelius Csar Jude H. Salinas; Jann-Yenq Liu; Charles C.H. Lin (Advances in Space Research, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Application of antimicrobial nanocomposite film packaging on the postharvest quality and specific spoilage organisms of mushrooms (Russula virescens) - Bifen Zhu; Yudi Liu; Margaret Brennan; Charles Brennan; Yuyue Qin; Lin Li; Haiyan Chen (Food Control, 2024)

Quality and microbial community changes in three kinds of Boletus wild mushroom during cold storage - Yudi Liu; Charles Brennan; Kai Jiang; Lin Li; Yuyue Qin; Haiyan Chen (Postharvest Biology and Technology, 2023)

Using drone soundings to study the impacts and compositions of plumes from a gigantic coal-fired power plant - Yen-Chen Chen; Jia-Lin Wang; Chih-Yuan Chang; Ming-Tung Chuang; Charles C.-K. Chou; Xiang-Xu Pan; Yu-Jui Ho; Chang-Feng Ou-Yang; Wen-Tzu Liu; Chih-Chung Chang (Science of The Total Environment, 2023)

Variable characteristics of microbial communities and volatile organic compounds during post-harvest storage of wild morel mushrooms - Kai Jiang; Lin Li; Zhouhao Yang; Haiyan Chen; Yuyue Qin; Charles Brennan (Postharvest Biology and Technology, 2023)

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

Catalytically efficient Co-CoOx-Al2O3 interface for mild temperature fatty alcohol production via fatty acid transfer hydrogenation - Yi Chen; Yongsheng Zhang; Wei Lin; Xianglin Cheng; Jianshe Wang; Xiaolong Liu; Chunbao Charles Xu; Renfeng Nie (Fuel, 2023)

Organophosphate esters (OPEs) in the marine environment: Spatial distribution and profiles in French coastal bivalves - Yann Aminot; Lin Tao; Karine Héas-Moisan; Charles Pollono; Margaret O'Loghlin; Catherine Munschy (Chemosphere, 2023)

Mechanism of polycyclic aromatic hydrocarbons degradation in the rhizosphere of Phragmites australis: Organic acid co-metabolism, iron-driven, and microbial response - Ni-chen Zhang; Dan A; Yuan-qing Chao; Hai-Yan Li; Charles Li; Qing-qi Lin; Ya-ying Li; Rong-liang Qiu (Environmental Pollution, 2023)

Probing air pollution in the Taichung metropolitan area, Taiwan.Part 1: Comprehensive model evaluation and the spatial-temporal evolution of a PM2.5 pollution event - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Wei-Nai Chen; Chian-Yi Liu; Chih-Chung Chang (Atmospheric Research, 2023)

Embedded information of aerosol type, hygroscopicity and scattering enhancement factor revealed by the relationship between PM2.5 and aerosol optical depth - Kuo-En Chang; Ta-Chih Hsiao; Si-Chee Tsay; Tang-Huang Lin; Stephen M. Griffith; Chian-Yi Liu; Charles C.-K. Chou (Science of The Total Environment, 2023)

Yam Seep at Four-Way Closure Ridge: a prominent active gas seep system at the accretionary wedge SW offshore Taiwan - Yiting Tseng; Miriam Römer; Saulwood Lin; Thomas Pape; Christian Berndt; Tzu-Ting Chen; Charles K. Paull; David W. Caress; Gerhard Bohrmann (International Journal of Earth Sciences, 2023)
Hydroacoustic surveys at the accretionary wedge southwest of Taiwan reveal a confined active hydrocarbon seepage area of ~ 49,000 m 2 in ~ 1350 m water depth on the northern crest of the Four-Way Closure Ridge, which we call Yam Seep. In this study, multibeam and side-scan sonar data acquired during surveys with an autonomous underwater vehicle during an expedition with R/V Ocean Researcher I in 2017 showed that the area is characterized by rough topography and high seafloor backscatter. Seafloor observations with a video sled and sediment sampling with gravity corers and the MeBo seafloor drill rig during an expedition with R/V SONNE in 2018 revealed that the area is almost entirely covered by intensely fractured methane-derived carbonates, which indicate that seepage has been ongoing for thousands of years. Hydroacoustic anomalies (‘flares’) in the water column indicated the presence of several gas bubble emission sites mostly at the center and eastern flank of the area in 2019. Drilling through massive carbonates in the northwestern part of Yam Seep induced free gas escape from a depth of ~ 5.1 m. This suggests the presence of gas hydrates in the subsurface as the seep area is located well within the gas hydrate stability zone. The inter-disciplinary investigations of the Yam Seep demonstrate that upward migration of light hydrocarbons and seafloor discharge has a considerable influence on the seabed properties.

Thermomechanically micronized sugar beet pulp: Emulsification performance and the contribution of soluble elements and insoluble fibrous particles - Jiawei Lin; Zhong-Sheng Tang; Charles S. Brennan; Jayani Chandrapala; Wenhong Gao; Zhong Han; Xin-An Zeng (Food Research International, 2023)

Soil organic carbon, aggregation and fungi community after 44 years of no-till and cropping systems in the Central Great Plains, USA - James S. Lin; Marcos V. M. Sarto; Tiffany L. Carter; Dallas E. Peterson; Colleen Gura; Laura Mino; Megan Rohrs; Hallie Lucas; Jamie Clark; Charles W. Rice (Archives of Microbiology, 2023)

Elucidation of the cellulose nanocrystal-sugar beet pectin interactions for emulsification enhancement - Jiawei Lin; Zhong-Sheng Tang; Jayani Chandrapala; Charles Stephen Brennan; Zhong Han; Xin-An Zeng (Food Hydrocolloids, 2023)

Spatial and seasonal variations in the carbon and lead isotopes of PM2.5 in air of residential buildings and their applications for source identification - Chien-Cheng Jung; Yang-Hsueh Chen; Charles C.-K. Chou; Yi-Tang Huang; Kuan-Ting Lin (Environmental Pollution, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Spatial patterns and driving factors of carbon stocks in mangrove forests on Hainan Island, China - Yuchen Meng; Ruikun Gou; Jiankun Bai; David Moreno‐Mateos; Charles C. Davis; Luoma Wan; Shanshan Song; Hongsheng Zhang; Xiaoshan Zhu; Guanghui Lin (Global Ecology and Biogeography, 2022)
Aim Mangrove forests are important coastal wetlands for the blue carbon budget and play a significant role in mitigating global climate change. However, spatial patterns of carbon stocks in mangrove forests on an island scale have not been quantified owing to methodological limitations and lack of understanding of controlling factors. We took the entire Hainan Island as a case study and aimed to carry out a comprehensive investigation of the spatial patterns and driving factors of carbon stocks in mangrove forests. Location Southern China. Time period 2017–2020. Major taxa studied Mangrove forest. Methods The upscaling method combined with field surveys and Sentinel‐2 imagery analysis were used to compare different models for optimization of mangrove ecosystem carbon stock estimations. We also used structural equation modelling (SEM) to evaluate the factors driving the distributional patterns of mangrove carbon stocks on an island scale. Results The current total mangrove carbon stock of the entire Hainan Island was estimated to be 703,181 Mg C (with a mean density of 192 Mg C/ha), with the above‐ and below‐ground carbon stocks averaging at 44.7 and 147.3 Mg C/ha, respectively. The mangrove carbon storage in the north‐eastern region of the island was the highest and in the west region the lowest. Sediment nitrogen content and plant species diversity had the most positive driving effects on the distribution of total carbon stock for Hainan Island mangroves. Main conclusions The combination of field surveys and Sentinel‐2 imagery analysis can be applied to regional‐scale estimations of carbon stocks for mangrove forests. Spatial pattens of mangrove carbon stocks vary among locations on Hainan Island, and soil nutrient (especially nitrogen) availability is the dominant factor regulating carbon stock variations along the land‐to‐sea gradient. Our findings have significant implications for better understanding the distribution of mangrove carbon stocks and quantification of the global blue carbon budget.

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Dosimetric evaluation of a patient-specific 3D-printed oral positioning stent for head-and-neck radiotherapy - Susannah Cleland; Philip Chan; Benjamin Chua; Scott B. Crowe; Jodi Dawes; Lizbeth Kenny; Charles Lin; Elise Obereigner; Samuel C. Peet; Jamie V. Trapp; Tania Poroa; Tanya Kairn (Physical and Engineering Sciences in Medicine, 2021)

Time‐varying trends in frost indicators in the U.S. Southern Great Plains - Yongjun Zhang; Prasanna Gowda; David Brown; Charles Rice; Zachary Zambreski; Seth Kutikoff; Xiaomao Lin (International Journal of Climatology, 2021)
Climatic frost indicators, including the dates of the last spring frost (LSF), the dates of the first fall frost (FFF), and the length of the frost‐free season (FFSL), are critical factors in anthropogenic and natural ecosystem management and can be directly calculated from daily minimum temperatures. Daily minimum temperature from the Applied Climate Information System was used to determine long‐term trends of frost indicators across the U.S. Southern Great Plains. The results demonstrated statistically significant trends of earlier LSF in eastern Kansas, western and eastern Oklahoma, and eastern Texas from 1950 to 2017. However, significantly later FFF trends and longer FFSL trends were mainly identified in eastern Oklahoma and eastern Texas. Overall, the region was characterized by the trends toward earlier LSF, later FFF, and longer FFSL from 1950 to 2017. In addition, the choice of time period in the climatic time series played an important role in LSF, FFF, and FFSL trends. Furthermore, the results from the correlation analysis of LSF and FFF with multiple climate indices indicated that the increasing trends in the spring Arctic Oscillation (AO) were consistent with the earlier onset of spring in Kansas and Texas, and the fall Atlantic Multidecadal Oscillation (AMO) was positively correlated with the later FFF dates in Kansas.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Potential changes to the biology and challenges to the management of invasive sea lamprey Petromyzon marinus in the Laurentian Great Lakes due to climate change - Robert J. Lennox; Gale A. Bravener; Hsien‐Yung Lin; Charles P. Madenjian; Andrew M. Muir; Christina K. Remucal; Kelly F. Robinson; Andrew M. Rous; Michael J. Siefkes; Michael P. Wilkie; Daniel P. Zielinski; Steven J. Cooke (Global Change Biology, 2020)
Control programs are implemented to mitigate the damage caused by invasive species worldwide. In the highly invaded Great Lakes, the climate is expected to become warmer with more extreme weather and variable precipitation, resulting in shorter iced‐over periods and variable tributary flows as well as changes to pH and river hydrology and hydrogeomorphology. We review how climate change influences physiology, behavior, and demography of a damaging invasive species, sea lamprey ( Petromyzon marinus ), in the Great Lakes, and the consequences for sea lamprey control efforts. Sea lamprey control relies on surveys to monitor abundance of larval sea lamprey in Great Lakes tributaries. The abundance of parasitic, juvenile sea lampreys in the lakes is calculated by surveying wounding rates on lake trout ( Salvelinus namaycush ), and trap surveys are used to enumerate adult spawning runs. Chemical control using lampricides (i.e., lamprey pesticides) to target larval sea lamprey and barriers to prevent adult lamprey from reaching spawning grounds are the most important tools used for sea lamprey population control. We describe how climate change could affect larval survival in rivers, growth and maturation in lakes, phenology and the spawning migration as adults return to rivers, and the overall abundance and distribution of sea lamprey in the Great Lakes. Our review suggests that Great Lakes sea lamprey may benefit from climate change with longer growing seasons, more rapid growth, and greater access to spawning habitat, but uncertainties remain about the future availability and suitability of larval habitats. Consideration of the biology of invasive species and adaptation of the timing, intensity, and frequency of control efforts is critical to the management of biological invasions in a changing world, such as sea lamprey in the Great Lakes.

Effects of antiepileptic drugs on lipogenic gene regulation and hyperlipidemia risk in Taiwan: a nationwide population-based cohort study and supporting in vitro studies - Yi-Wen Li; Chung-Hsing Wang; Chao-Jung Chen; Charles C. N. Wang; Cheng-Li Lin; Wai-Kok Cheng; Hsin-Yi Shen; Yun-Ping Lim (Archives of Toxicology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Transcriptional responses of the marine green alga Micromonas pusilla and an infecting prasinovirus under different phosphate conditions - Charles Bachy; Christina J. Charlesworth; Amy M. Chan; Jan F. Finke; Chee‐Hong Wong; Chia‐Lin Wei; Sebastian Sudek; Maureen L. Coleman; Curtis A. Suttle; Alexandra Z. Worden (Environmental Microbiology, 2018)
Summary Prasinophytes are widespread marine algae for which responses to nutrient limitation and viral infection are not well understood. We studied the picoprasinophyte, Micromonas pusilla , grown under phosphate‐replete (0.65 ± 0.07 d −1 ) and 10‐fold lower (low)‐phosphate (0.11 ± 0.04 d −1 ) conditions, and infected by the phycodnavirus MpV‐SP1. Expression of 17% of Micromonas genes in uninfected cells differed by >1.5‐fold ( q

Burly1 is a mouse QTL for lean body mass that maps to a 0.8-Mb region of chromosome 2 - Cailu Lin; Brad D. Fesi; Michael Marquis; Natalia P. Bosak; Anna Lysenko; Mohammed Amin Koshnevisan; Fujiko F. Duke; Maria L. Theodorides; Theodore M. Nelson; Amanda H. McDaniel; Mauricio Avigdor; Charles J. Arayata; et al. (Mammalian Genome, 2018)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Detection of mycobacterial and viral DNA in Kikuchi-Fujimoto disease: an analysis of 153 Chinese pediatric cases - Zhe Xu; Ying Liu; Haijing Li; Shufang Meng; Alan S. Boyd; Charles W. Stratton; Lin Ma; Yi-Wei Tang (Science China Life Sciences, 2017)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

Metabolic activation of furan moiety makes Diosbulbin B hepatotoxic - Weiwei Li; Dongju Lin; Huiyuan Gao; Youjun Xu; Dongya Meng; Charles Vincent Smith; Ying Peng; Jiang Zheng (Archives of Toxicology, 2016)

Mechanism-Based Pharmacokinetic Modeling to Evaluate Transporter-Enzyme Interplay in Drug Interactions and Pharmacogenetics of Glyburide - Manthena V. S. Varma; Renato J. Scialis; Jian Lin; Yi-An Bi; Charles J. Rotter; Theunis C. Goosen; Xin Yang (The AAPS Journal, 2014)

Critical mechanisms for the formation of extreme arctic sea-ice extent in the summers of 2007 and 1996 - Xiquan Dong; Behnjamin J. Zib; Baike Xi; Ryan Stanfield; Yi Deng; Xiangdong Zhang; Bing Lin; Charles N. Long (Climate Dynamics, 2014)

Identification of a stable molecular signature in mammary tumor endothelial cells that persists in vitro - Lin Xiao; J. Chuck Harrell; Charles M. Perou; Andrew C. Dudley (Angiogenesis, 2014)

High Sensitivity Micro-Elastometry: Applications in Blood Coagulopathy - Gongting Wu; Charles R. Krebs; Feng-Chang Lin; Alisa S. Wolberg; Amy L. Oldenburg (Annals of Biomedical Engineering, 2013)

Comparison of point and array-computed rotations for the TAIGER explosions of 4 March 2008 - Lauren M. Kendall; Charles A. Langston; W. H. K. Lee; C. J. Lin; C. C. Liu (Journal of Seismology, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Bait worm packaging as a potential vector of invasive species - Christina L. Haska; Charles Yarish; George Kraemer; Noreen Blaschik; Robert Whitlatch; Huan Zhang; Senjie Lin (Biological Invasions, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Tissue factor expression in ovarian cancer: implications for immunotherapy with hI-con1, a factor VII-IgGFc chimeric protein targeting tissue factor - Emiliano Cocco; Joyce Varughese; Natalia Buza; Stefania Bellone; Ken-Yu Lin; Marta Bellone; Paola Todeschini; Dan-Arin Silasi; Masoud Azodi; Peter E. Schwartz; Thomas J. Rutherford; Luisa Carrara; et al. (Clinical & Experimental Metastasis, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Functional evaluation of therapeutic response for a mouse model of medulloblastoma - Aislynn K. Samano; Sachiko Ohshima-Hosoyama; Thomas G. Whitney; Suresh I. Prajapati; Aoife Kilcoyne; Eri Taniguchi; William W. Morgan; Laura D. Nelon; Ai-Ling Lin; Osamu Togao; Inkyung Jung; Brian P. Rubin; et al. (Transgenic Research, 2010)

Hydrological and biogeochemical controls on the timing and magnitude of nitrous oxide flux across an agricultural landscape - MICHAEL J. CASTELLANO; JOHN P. SCHMIDT; JASON P. KAYE; CHARLES WALKER; CHRIS B. GRAHAM; HENRY LIN; CURTIS J. DELL (Global Change Biology, 2010)
Anticipated increases in precipitation intensity due to climate change may affect hydrological controls on soil N 2 O fluxes, resulting in a feedback between climate change and soil greenhouse gas emissions. We evaluated soil hydrologic controls on N 2 O emissions during experimental water table fluctuations in large, intact soil columns amended with 100 kg ha −1 KNO 3 ‐N. Soil columns were collected from three landscape positions that vary in hydrological and biogeochemical properties ( N = 12 columns). We flooded columns from bottom to surface to simulate water table fluctuations that are typical for this site, and expected to increase given future climate change scenarios. After the soil was saturated to the surface, we allowed the columns to drain freely while monitoring volumetric soil water content, matric potential and N 2 O emissions over 96 h. Across all landscape positions and replicate soil columns, there was a positive linear relationship between total soil N and the log of cumulative N 2 O emissions ( r 2 = 0.47; P = 0.013). Within individual soil columns, N 2 O flux was a Gaussian function of water‐filled pore space (WFPS) during drainage (mean r 2 = 0.90). However, instantaneous maximum N 2 O flux rates did not occur at a consistent WFPS, ranging from 63% to 98% WFPS across landscape positions and replicate soil columns. In contrast, instantaneous maximum N 2 O flux rates occurred within a narrow range (−1.88 to −4.48 kPa) of soil matric potential that approximated field capacity. The relatively consistent relationship between maximum N 2 O flux rates and matric potential indicates that water filled pore size is an important factor affecting soil N 2 O fluxes. These data demonstrate that matric potential is the strongest predictor of the timing of N 2 O fluxes across soils that differ in texture, structure and bulk density.

Applications of Satellite-Derived Ocean Measurements to Tropical Cyclone Intensity Forecasting - Gustavo Goni; Mark DeMaria; John Knaff; Charles Sampson; Isaac Ginis; Francis Bringas; Alberto Mavume; Chris Lauer; I.I. Lin; M.M. Ali; Paul Sandery; Silvana Ramos-Buarque; et al. (Oceanography, 2009)

Sulforaphane inhibits TNF-α-induced activation of p38 MAP kinase and VCAM-1 and MCP-1 expression in endothelial cells - Xi-Lin Chen; Geraldine Dodd; Charles Kunsch (Inflammation Research, 2009)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

Uptake of Different Species of Iodine by Water Spinach and Its Effect to Growth - Huan-Xin Weng; Ai-Lan Yan; Chun-Lai Hong; Lin-Li Xie; Ya-Chao Qin; Charles Q. Cheng (Biological Trace Element Research, 2008)

Nitrogen versus phosphorus limitation of phytoplankton growth in Ten Mile Creek, Florida, USA - Youjian Lin; Zhenli He; Yuangen Yang; Peter J. Stoffella; Edward J. Phlips; Charles A. Powell (Hydrobiologia, 2008)

Evaluation of a new sitting concept designed for prevention of pressure ulcer on the buttock using finite element analysis - Dohyung Lim; Fang Lin; Ronald W. Hendrix; Brian Moran; Charles Fasanati; Mohsen Makhsous (Medical & Biological Engineering & Computing, 2007)

Release of intracellular Zn2+ in cultured neurons after brief exposure to low concentrations of exogenous nitric oxide - Wei Lin; Bhavana Mohandas; Charles P. Fontaine; Robert A. Colvin (BioMetals, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Optical Imaging of the Adoptive Transfer of Human Endothelial Cells in Mice Using Anti-Human CD31 Monoclonal Antibody - Alexei A. Bogdanov; Charles P. Lin; Hye-Won Kang (Pharmaceutical Research, 2007)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

Expression of a transcription factor from Capsicum annuum in pine calli counteracts the inhibitory effects of salt stress on adventitious shoot formation - Wei Tang; Ronald J. Newton; Jinxing Lin; Thomas M. Charles (Molecular Genetics and Genomics, 2006)

Evaluation of Candidate Gene Effects for Beef Backfat via Bayesian Model Selection - Xiao-Lin Wu; Michael D. MacNeil; Sachinadan De; Qian-Jun Xiao; Jennifer J. Michal; Charles T. Gaskins; Jerry J. Reeves; Jan R. Busboom; Raymond W. Wright; Zhihua Jiang (Genetica, 2005)

Excavating Y-chromosome haplotype strata in Anatolia - Cengiz Cinnioglu; Roy King; Toomas Kivisild; Ersi Kalfoglu; Sevil Atasoy; Gianpiero L. Cavalleri; Anita S. Lillie; Charles C. Roseman; Alice A. Lin; Kristina Prince; Peter J. Oefner; Peidong Shen; et al. (Human Genetics, 2004)

Precipitation from vertical motion: a statistical diagnostic scheme - Brian E. J. Rose; Charles A. Lin (International Journal of Climatology, 2003)
The relationship between precipitation and atmospheric vertical motion is investigated over the globe. By combining and averaging precipitation rates within small ranges of vertical motion, the mean precipitation rate is found to vary smoothly with vertical motion. The relationship is modelled with a simple function that assumes zero precipitation for subsidence and linearly increasing precipitation for ascending motion. Function parameters are computed from National Centers for Environmental Prediction reanalysis data individually for every grid point and calendar month. Variations in the slope account for geographical and seasonal variations in moisture and other precipitation factors. At each grid point, the scheme diagnoses precipitation rate from a single concurrent value of vertical motion. It is shown to have moderate skill over climatology in predicting mean monthly precipitation. The midlatitudes, oceans and the winter season are favoured. The scheme is designed to extract precipitation fields from a dry general circulation model, based on the simulated vertical motion. Application to climate modelling is discussed. Copyright © 2003 Royal Meteorological Society

Lipase-catalyzed glycerolysis of an oil rich in eicosapentaenoic acid residues - Carlos Torres; Betty Lin; Charles G. Hill (Biotechnology Letters, 2002)

Interstitial colocalization of two cervid satellite DNAs involved in the genesis of the Indian muntjac karyotype - Yueh-Chun Li; Charles Lee; Despina Sanoudou; Tzong-Hsiung Hsu; Shuan-Yow Li; Chyi-Chyang Lin (Chromosome Research, 2000)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Conservation of Human Gamma-X Centromeric Satellite DNA Among Primates with an Autosomal Localization in Certain Old World monkeys - Charles Lee; Roscoe Stanyon; Chyi-chyang Lin; Malcolm A. Ferguson-smith (Chromosome Research, 1999)

Seasonal Patterns of Plant Flammability and Monoterpenoid Content in Juniperus ashei - M. Keith Owens; Chii-Dean Lin; Charles A. Taylor; Steven G. Whisenant (Journal of Chemical Ecology, 1998)